Grain Sorghum Cost-Return Budget in North Central Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2001)
This publication provides estimated cost and returns for forward farm planning for grain sorghum in north central Kansas.
MF2159_2001_10
Keywords: MF2159; Crops; Economics; MF